2015
DOI: 10.3382/ps/pev039
|View full text |Cite
|
Sign up to set email alerts
|

On-farm comparison of keel fracture prevalence and other welfare indicators in conventional cage and floor-housed laying hens in Ontario, Canada

Abstract: The objective of this study was to compare the flock-level prevalence of healed keel bone fractures and to benchmark other indicators of well-being in laying hens housed in conventional cages and single-tier floor housing systems at several points during the production period. Commercial farms in Ontario, Canada, that housed hens in cages (n=9) or floor barns (n=8) were included. Flocks were beak-trimmed brown hens of various strains. Each flock was visited at 20, 35, 50, and 65 wk of age. At each visit, 50 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
84
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 27 publications
10
84
1
1
Order By: Relevance
“…All types of production system experience the problem although cagefree systems have been reported to have the highest occurrence of the problem. Prevalences in non-cage systems have been reported to range from 70 and up to 97% [3][4][5][6][7][8]. However, high prevalences, up to 62%, also has been reported from enriched cages [7,9] PLOS ONE PLOS ONE | https://doi.org/10.1371/journal.pone.0229735 March 9, 2020 1 / 15 a1111111111 a1111111111 a1111111111 a1111111111 a1111111111…”
Section: Introductionmentioning
confidence: 99%
“…All types of production system experience the problem although cagefree systems have been reported to have the highest occurrence of the problem. Prevalences in non-cage systems have been reported to range from 70 and up to 97% [3][4][5][6][7][8]. However, high prevalences, up to 62%, also has been reported from enriched cages [7,9] PLOS ONE PLOS ONE | https://doi.org/10.1371/journal.pone.0229735 March 9, 2020 1 / 15 a1111111111 a1111111111 a1111111111 a1111111111 a1111111111…”
Section: Introductionmentioning
confidence: 99%
“…One type of KBD, keel fractures (KF), sometimes referred to as 'old breaks', can be defined as breaks in the bone that will typically manifest as a callus around the fracture site after a few days; KF may also involve sharp, unnatural deviations, or bending of the bone (Wilkins et al, 2004). The problem of keel damage is clearly widespread with similar yet highly variable levels reported in various countries, such as Switzerland (Kappeli et al, 2011); UK (Wilkins et al, 2011); The Netherlands, Belgium, Germany (Rodenburg et al, 2008;Heerkens et al, 2013) and Canada (Petrik et al, 2015). Keel bone damage (KBD) extends across genetic lines (Kappeli et al, 2011) and all types of housing systems (Wilkins et al, 2011;Petrik et al, 2015)including organic production systems (Bestman and Wagenaar, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some researchers (43) reported that feather pecking, high mortality levels and keel bone fractures were significant welfare problems in non-cage rearing systems for laying hens. Petrik et al (34) compared two systems which are floor and cage. They reported that plumage condition was not affected by rearing system.…”
Section: Discussionmentioning
confidence: 99%